A Novel Temporal Bone Simulation Model Using 3D Printing Techniques. Issue 9 (October 2015) - Mowry, Sarah E.; Jammal, Hachem; Myer, Charles; Solares, Clementino Arturo; Weinberger, Paul
Abstract : Hypothesis: An inexpensive temporal bone model for use in a temporal bone dissection laboratory setting can be made using a commercially available, consumer-grade 3D printer. Background: Several models for a simulated temporal bone have been described but use commercial-grade printers and materials to produce these models. The goal of this project was to produce a plastic simulated temporal bone on an inexpensive 3D printer that recreates the visual and haptic experience associated with drilling a human temporal bone. Methods: Images from a high-resolution CT of a normal temporal bone were converted into stereolithography files via commercially available software, with image conversion and print settings adjusted to achieve optimal print quality. The temporal bone model was printed using acrylonitrile butadiene styrene (ABS) plastic filament on a MakerBot 2x 3D printer. Simulated temporal bones were drilled by seven expert temporal bone surgeons, assessing the fidelity of the model as compared with a human cadaveric temporal bone. Using a four-point scale, the simulated bones were assessed for haptic experience and recreation of the temporal bone anatomy. Results: The created model was felt to be an accurate representation of a human temporal bone. All raters felt strongly this would be a good training model for junior residents or to simulate difficult surgical anatomy. Material cost for each model was 1.92. Conclusions: A realistic, inexpensive, and easily reproducible temporal bone model can be created on a consumer-grade desktop 3D printer. Abstract : Supplemental Digital Content is available in the text